Menjadi Guru Yang Siap Di Masa Pandemi Covid-19, Melalui Penggunaan Google Meet Dan Google Classroom Pada Pembelajaran Daring - Setiawan, Wahyu (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
Online learning is an adaptation of face-to-face learning which cannot be carried out during the covid-19 pandemic, therefore conditioning online learning properly without changing the meaning of face-to-face learning is something that a teacher must prepare. The equitable support facilities owned by teachers and students at SDN Kutolawas is an excellent opportunity to condition this technology-based learning. However, most of the learning process that occurs still uses social media, namely wa groups. The purpose of holding this learning is to equip and provide additional platform options in the application of online learning. So that teachers can innovate and be creative in the online teaching process during this pandemic. The method given is in the form of using the Google Meet and Google Classroom applications.